Differential responses of trailing-edge populations of a foundation alga to thermal stress. Issue 4 (2nd October 2021) - García, Ana G.; Olabarria, Celia; Álvarez-Losada, Óscar; Viejo, Rosa M.
ABSTRACT: Populations within the same species range edge may experience contrasting local conditions and exhibit diverse levels of environmental tolerance. This heterogeneity within a range boundary has seldom been considered in studies forecasting the impact of anthropogenic habitat alteration and climate change on species distributions. Moreover, any ecological prediction under changing environmental conditions requires a good understanding of the combined responses of organisms to multiple stressors, in particular the effects on key life cycle stages of species. The intertidal seaweed Fucus serratus is a dominant species on northern Atlantic shores and whose southern limit is in the NW Iberian Peninsula. We examined how early developmental stages of southern-edge populations of this foundation alga responded to the combined effects of environmental stressors, including salinity and aerial and seawater temperature. Four populations from two different areas of the NW Iberian coast were considered: two populations from open shores on the northern coast and two populations from the western rias on the Atlantic coast. The study findings revealed inter-population variability in the response to heat stress, with greater survival of germlings from the northern populations than those from western rias. Environmental conditions are still more benign within western rias, under the influence of strong summer upwelling events. The results also suggest the key role of aerial thermal stress in determining the southern limit of distribution of the target species. The future of these heterogeneous edge populations from NW Iberian Peninsula depends on trends in climate change and the ability of populations to cope with these. Environmental changes may already be occurring at rates that exceed the plastic and adaptive potential of edge populations in N Spain, while the future of western rias as climate refugia for this and other foundation alga is also uncertain.